When calls the heart. Second chances [videorecording (DVD)] - Fearnley, Neill; Krakow, Erin; Willett, Chad; Horsdal, Chelah, 1973-; Lissing, Daniel, 1981-; Loughlin, Lori; Oke, Janette, 1935- (Frontier Productions : Millennium Entertainment, 2014)
"Jack's ... feelings for Elizabeth ... develop beyond friendship and he finally asks her out on a date. Meanwhile, the town prepares for the return of Adam Miller, the lone survivor of the mine disaster"--Container.